Determinants of De Novo New Entrant Survival in the Liberalized Intra-European Scheduled Passenger Airline Industry - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2009)
This paper analyzes semi-parametrically the survival odds of de novo entrants in the liberalized intra-European scheduled passenger airline industry with respect to three sets of determinants: strategic positioning, inaugural market entry and network economics. Among these determinants, a [`]low-cost' strategic position does not confer survival benefits to new entrants. Entering markets with different levels of prior concentrations - which economists traditionally relate to different pricing powers - does not significantly affect the survival odds of new entrants. Entering mid-sized markets adversely affects entrant survival, while entering large, small or new markets at inception does not noticeably impact entrant survival. Network economics that corresponds to low operating costs (aircraft size) is a consistent contributor to entrant survival. In addition, new entrants based in France or Ireland are less likely to survive than others, reflecting the strong negative impact of intermodal competition and a strong, entrenched entrant.